Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan PT. Epson - Jumawan Jumawan; Edy Soesanto; Bukhari Al Fizikri; Nawfa Ayu Nazira; Nurul Syah Nasyid Firdauzy; Rini Nurmila Sari; Siti Habibah; Zulfah Yuliani (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
Motivation and discipline are closely related to employee performance. The motivation and discipline that is continuously instilled in a trainee can raise and lower their performance at work or discourage them. The productivity of any institution will increase as a result of motivated and disciplined workers. The observation was conducted at PT Epson Indonesia. The purpose of this observation is to understand the relationship between work motivation and work discipline and the variables that distinguish between the two that have the greatest influence on employee performance. The observation system used is quantitative observation. Materials are generated from interviews using questionnaires. The observation results show that motivation and work discipline have an impact on employee performance. By using this result, it shows that work discipline has more impact on employee performance of PT Epson Indonesia.